Hyper-stable collective rankings - Laine, Jean (Elsevier Science Bv, 2015)
We introduce a new consistency property for social welfare functions (SWF), called hyper-stability. An SWF is hyper-stable if at any profile over finitely many alternatives where a weak order R is chosen, there exists a profile of linear orders over linear orders, called hyper-profile, at which only linearizations of R are ranked first by the SWF. Profiles induce hyper-profiles according to some minimal compatibility conditions. We provide sufficient conditions for hyper-stability, and we investigate hyper-stability for several Condorcet SWFs. An important conclusion is that there are non-dictatorial hyper-stable SWFs. (C) 2015 Elsevier B.V. All rights reserved.